ISSUES OF LANGUAGE DEVELOPMENT FROM THE POINT OF VIEW OF THE PRESIDENT OF THE REPUBLIC OF UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
The issue of the activism of languages in society is one of the important issues of State policy. Proper implementation of the language policy in society will contribute to the activation and development of languages, serve to improve friendly relations between the peoples of a multinational society. This article discusses the issue of language policy in the independent society of Uzbekistan and the point of view of the First President of the Republic of Uzbekistan I.A.Karimov and the current President of Uzbekistan G.M.Mirziyoyev is discussed and considered to improve the development of the state language and languages of national minorities.